Penerapan Prinsip-Prinsip Good Governance (Studi Kasus dalam Proses Pengangkatan Pejabat Struktural Eselon II di Lingkungan Pemerintah Kota Bandar Lampung) - Andre Pebrian Perdana (Balitbangda Provinsi Lampung, 2017)
Appointment of civil servants in the structural positions should comply to the principles of good governance, but in practice it was still dominated by various political interests, kinship and the intervention of any outside organization system of the Government. The formulation of the problem of the research was: